Castilla y León 1898 - 1998. - Arufe, Josefa Eugenia Fernández; De La Casa, Carlos; De Diego, Emilio; Fuertes, Juan Velarde; Lucas, Juan José (Valladolid : Junta de Castilla y León, 1998)
Zuloaga, Daniel ; Pereda, Federico ; Santamaria, Marceliano ; Tolin, Dióscore T. de la Puebla ; Izarra, S. Cabello ; Armesto, Primitico Alvarez ; Mañanos, Asterio ; Oliva, Eugenio ; Martin, Antonio Carnero ; Tejedor, Alcazar ; Maureta, G. ; Rodriguez ; Peña, Maximino ; Carrilero, Enrique ; Lesmes, Amelio Garcia ; Gomez, Gabriel Osmundo ; Ocaña, Miguel Jadraque y Sánchez ; Lozano, José Alvarez ; Alcahud, Gloria ; Alonso, Jesús ; Vaquerizo, José Maria Antolín ; Arenillas, Armando ; Barreiro, Toño ; Salinero, Jerónimo Bueno ; Colomo, Lorenzo ; Recio, Felix Curto ; Requejo, Angel Duque ; Evangelista, Carlos ; Omaña, Alfredo ; Girait, Juan ; Martin, Rafael Guzmán ; de Horna, Luis ; Rodriguez, Jesús Angel Martinez ; Alvarez, Juan Carlos Matilia ; Núñez, Anibal ; Sánchez, Carlos Piñel ; Ransa, Pablo ; Saez, Luis ; Aldea, Carlos Sanz ; Fuente, Antonio Sanz de la ; Tapia, Ramiro ; Vidal, Jorge ; Villar, Isabel ; Guedón, Ana Zaragozá
Castilla y León 1898 - 1998, Monasterio de Nuestra Sra. de Prado, Valladolid, del 23 de junio al 23 de agosto de 1998
Spaans
kunstcatalogus
Keywords: Spanje